2019
DOI: 10.1002/oby.22580
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Empirically Based Model for Understanding Future Trends in US Obesity Prevalence in the Context of Social Influences

Abstract: ObjectiveThis study aimed to (1) identify mechanistic model structures that produced quality fit to historic obesity prevalence trends and (2) evaluate the sensitivity of future obesity prevalence to social transmission and nonsocial parameters.MethodsAn age‐ and gender‐structured compartmental model was used to describe transitions between weight status groups. Four model structures with different combinations of social transmission and nonsocial mechanisms were calibrated to match historic time series and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Our results are more comparable to the Esteban study in France, which is based on measured anthropometrics and shows that from 2006 to 2015, obesity prevalence has been relatively stable at around 17% in adults’ men and women. In fact, data from several countries show a decline or stabilization of obesity levels, albeit with a mixed evidence, data from 2015 to 2016 prevalence indicating no evidence of a decline in obesity at any age 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are more comparable to the Esteban study in France, which is based on measured anthropometrics and shows that from 2006 to 2015, obesity prevalence has been relatively stable at around 17% in adults’ men and women. In fact, data from several countries show a decline or stabilization of obesity levels, albeit with a mixed evidence, data from 2015 to 2016 prevalence indicating no evidence of a decline in obesity at any age 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the reason behind such an increase among young individuals and no other remains to be determined, the result of such an increase in Constances could be attributed to peer social transmission and non-social mechanisms. Researchers studying dynamic simulation models to understand how underlying population age structure and different mechanisms influence trends of obesity, have shown that obesity prevalence was most sensitive to adult parameters (such as social interactions, interplay of individual behaviors and norms) 15 . Our results show a somehow lower prevalence of obesity in the four study points compared to the Esteban study which was also based on measured anthropometrics and has found a prevalence of obesity of 17% in adults aged 18–74 years.…”
Section: Discussionmentioning
confidence: 99%